Factor XIa-triggered thrombin generation in severe haemophilia A - Desborough, M; Naeem, H; Baker, P; Curry, N (John Wiley & Sons Ltd, 2018)
Severe haemophilia A is associated with a severe bleeding phenotype (Richards et al, 2010). The factor VIII (FVIII) level is the mainstay of investigation and monitoring for these patients. However, there are often inconsistencies between the FVIII level and bleeding phenotype in haemophilia A (Franchini et al, 2009). Consequently, other tests have been under investigation to determine if they might have superior predictive value for assessing the bleeding risk for patients with haemophilia A.